2020
DOI: 10.7759/cureus.8122
|View full text |Cite
|
Sign up to set email alerts
|

Adult Double-Chambered Right Ventricle Associated With Ventricular Tachycardia and New-Onset Heart Failure

Abstract: A double-chambered right ventricle is an uncommon form of congenital heart disease that is characterized by the division of the right ventricle into a proximal high-pressure chamber and a distal low-pressure chamber. A 70-year-old male presented to the emergency room from his outpatient doctor's office with unstable wide complex ventricular tachycardia with right axis deviation. His ventricular tachycardia was terminated using external cardioversion and intravenous amiodarone. He was subsequently found to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 11 publications
0
6
0
6
Order By: Relevance
“…Spironolactone: Spironolactone, an aldosterone inhibitor originally used as an effective diuretic for the treatment of high blood pressure and edema, was subsequently shown to benefit patients with heart failure. [369][370][371] Increasingly, studies have shown the anticancer properties of spironolactone on prostate and breast cancer. 372,373 Regulation of DNA damage response appears to be the key mechanism of spironolactone in cancer treatment.…”
Section: Non-oncology Drugs In Drug Repurposingmentioning
confidence: 99%
“…Spironolactone: Spironolactone, an aldosterone inhibitor originally used as an effective diuretic for the treatment of high blood pressure and edema, was subsequently shown to benefit patients with heart failure. [369][370][371] Increasingly, studies have shown the anticancer properties of spironolactone on prostate and breast cancer. 372,373 Regulation of DNA damage response appears to be the key mechanism of spironolactone in cancer treatment.…”
Section: Non-oncology Drugs In Drug Repurposingmentioning
confidence: 99%
“…Therefore, the relationship between spironolactone and the treatment of hair loss is related to the role of spironolactone in reducing androgens. 8,22 It was reported that spironolactone could reduce the symptoms of FPHL not only in adult women but also in a nine-year-old girl. 23 Meanwhile, studies have shown different results regarding the efficacy of finasteride.…”
Section: Discussionmentioning
confidence: 99%
“…With the reduction in androgen production, hair that has become thin and weak due to high secretion of these hormones becomes thick again and returns to its normal state. Therefore, the relationship between spironolactone and the treatment of hair loss is related to the role of spironolactone in reducing androgens 8,22 . It was reported that spironolactone could reduce the symptoms of FPHL not only in adult women but also in a nine‐year‐old girl 23 …”
Section: Discussionmentioning
confidence: 99%
“…This side effect is higher risk in individuals >45 years of age or with underlying renal disease (Hayes et al, 2022). It may also be associated with polyuria, orthostasis, and drowsiness (Patibandla et al, 2023). Lastly, there is some concern for premature breast bud fusion with spironolactone, although this concern requires further investigation (Wierckx et al, 2014).…”
Section: Introductionmentioning
confidence: 99%